1997
DOI: 10.1097/00007890-199704150-00019
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION OF CTLA4-Ig BY BIOLISTICALLY TRANSFECTED MOUSE ISLETS PROMOTES ISLET ALLOGRAFT SURVIVAL1

Abstract: Transfection of allogeneic mouse islets with human CTLA4-Ig results in prolonged allograft survival. Although on histology mononuclear cells are present in the area of the transfected graft, they do not appear to infiltrate or destroy the islet graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Administration of a high dose of CTLA4-Ig was previously reported to suppress immune responses systemically [14,15,16,17], and several preceding studies indicate that local delivery of CTLA4-Ig prolongs the survival of islet allografts in mice [8,9,18]. Using adenovirus-mediated expression of CTLA4-Ig, investigators [26] recently reported that the production of CTLA4-Ig by islet cells themselves, but not by cells located in remote sites, is effective in prolonging islet allograft survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of a high dose of CTLA4-Ig was previously reported to suppress immune responses systemically [14,15,16,17], and several preceding studies indicate that local delivery of CTLA4-Ig prolongs the survival of islet allografts in mice [8,9,18]. Using adenovirus-mediated expression of CTLA4-Ig, investigators [26] recently reported that the production of CTLA4-Ig by islet cells themselves, but not by cells located in remote sites, is effective in prolonging islet allograft survival.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that the site-specific delivery of immunosuppressive molecules could provide an alternative strategy to avoid the hazardous side effects of conventional immunosuppressants [6,7,8,9]. Various immunosuppressive molecules have been tested in a variety of transplantation models and need to be assessed for their effectiveness on graft prolongation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A bimodal response has similarly been observed in other studies based on a local administration of CTLA4Ig. 14,15,33,34 The explanation for this response remains unclear. The expression level of CTLA4Ig may have to reach a threshold value in order to diffuse up to the regional lymph nodes and exert its immunomodulating effect.…”
Section: Figure 8 Photomicrographs Of Both Hind Limbs From a Dba/2j Mmentioning
confidence: 99%
“…13 The local delivery of CTLA4Ig was recently investigated in various cell transplantation protocols of islet allotransplantation: islets were either coated with CTLA4Ig before implantation 14 or genetically modified by biolistical transfection. 15 Co-transplantation of syngeneic C 2 C 12 myoblasts expressing CTLA4Ig together with allogeneic islets prolonged their survival under the mouse kidney capsule. 16 Adenoviral transduction of CTLA4Ig expression was reported to improve the survival of myeloid dendritic cells in allogeneic recipients significantly, 17 as well as pancreatic islets in xenogeneic recipients.…”
Section: Introductionmentioning
confidence: 99%